ChemInform Abstract: Single Crystal Growth and Structural Characterization of Four Complex Uranium Oxides: CaUO4, β‐Ca3UO6, K4CaU3O12, and K4SrU3O12. Issue 22 (13th May 2013) - Read, Cory M.; Bugaris, Daniel E.; zur Loye, Hans‐Conrad
Abstract Single crystals of CaUO4 (I), β‐Ca3UO6 (II), K4CaU3O12 (III), and K4SrU3O12 (IV) are grown from UO2 or U3O8 in a K2CO3 flux in the presence or absence of CaCO3 or SrCO3 (alumina crucible, 900—1050 °C, 24—48 h).